Sinergi Pengelolaan Zakat dan Wakaf Produktif dengan Mengembangkan Lembaga Keuangan Mikro Finance Syariah di Indonesia - Awaluddin Awaluddin; Rina Anggraini; Vewi Julita; Iiz Izmuddin; Rusyaida Rusyaida (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
This research is entitled Synergy for the Management of Productive Zakat and Waqf with the Development of Sharia Micro Finance by using descriptive research methods with a qualitative approach. The sources of data in this study are in the form of observation and reviewing several books and readings related to this discussion and comparing them with expert opinions and materials from seminars that discuss the issues under study. Data analysis was carried out qualitatively by interpreting data, facts and information that had been collected through intellectual understanding empirically and then studied in an in-depth way so as to produce a picture of the actual data. The management of zakat and productive waqf is generally under the control of amil zakat agencies and waqf institutions through Nazir waqf. The formula developed in the management of zakat and waqf has not been unified and combined in the management aspect between zakat management and waqf management. The utilization of productive zakat and waqf through Islamic microfinance institutions can be described by a model of adjusting zakat and waqf management in the aspect of zakat and productive waqf utilization through Islamic microfinance institutions. With the adjustment model of zakat and waqf management, it will be expected to give birth to an agreement in the management of zakat and productive waqf through sharia microfinance institutions